CURRENT PROBLEMS OF THE AUDIT OF CONSOLIDATED FINANCIAL REPORTING - Shaukerova, Z.M.; Abdykerova, G.Zh.; Kasymova, A.G. (Academic Journal of Physical and Chemical Sciences, 2018)
Modernization of the economy of Kazakhstan, which is based on competitiveness, dictates further improvement of accounting methods and techniques. That will allow organizations to more realistically see their financial condition and show greater autonomy in solving problems and drawing up IFRS statements. As practice has shown, the transition to IFRS is a complex, ambiguous process. Under IFRS, there are very high requirements for ensuring transparency of information. Despite the fact that many countries use international standards as the basis for national accounting legislation, in each of them the application of IFRS has its own specifics due to differences in terminology, scope, classification and deadlines for their entry into force. However, there are a number of problems, for example, based on the consolidated financial statements, it is impossible to determine the contribution of an individual subsidiary to the financial position and financial performance of the group. The authors presented not only the problems of organizing an audit of the consolidated financial statements, but also suggested ways to solve them